Clinical outcomes from the CDC's Colorectal Cancer Screening Demonstration Program. (18th July 2013) - Seeff, Laura C.; Royalty, Janet; Helsel, William E.; Kammerer, William G.; Boehm, Jennifer E.; Dwyer, Diane M.; Howe, William R.; Joseph, Djenaba; Lane, Dorothy S.; Laughlin, Melinda; Leypoldt, Melissa; Marroulis, Steven C.; et al.
Abstract : BACKGROUND: Colorectal cancer remains the second leading cause of cancer‐related deaths among US men and women. Screening rates have been slow to increase, and disparities in screening remain. METHODS: To address the disparity in screening for this high burden but largely preventable disease, the Centers for Disease Control and Prevention (CDC) designed and established a 4‐year Colorectal Cancer Screening Demonstration Program (CRCSDP) in 2005 for low‐income, under‐insured or uninsured men and women aged 50 to 64 years in 5 participating US program sites. In this report, the authors describe the design of the CRCSDP and the overall clinical findings and screening test performance characteristics, including the positive fecal occult blood testing (FOBT) rate; the rates of polyp, adenoma, and cancer detection with FOBTs and colonoscopies; and the positive predicative value for polyps, adenomas, and cancers. RESULTS: In total, 5233 individuals at average risk and increased risk were screened for colorectal cancer across all 5 sites, including 44% who underwent screening FOBT and 56% who underwent screening colonoscopy. Overall, 77% of all individuals screened were women. The FOBT positivity rate was 10%. Results from all screening or diagnostic colonoscopies indicated that 75% had negative results and required a repeat screening colonoscopy in 10 years, 16% had low‐risk adenomas and required surveillance colonoscopy in 5 to 10 years, 8% had high‐risk adenomas and required surveillance colonoscopy in 3 years, and 0.6% had invasive cancers. CONCLUSIONS: This report documents the successes and challenges in implementing the CDC's CRCSDP and describes the clinical outcomes of this 4‐year initiative, the patterns in program uptake and test choice, and the comparative test performance characteristics of FOBT versus colonoscopy. Patterns in final outcomes from the follow‐up of positive screening tests were consistent with national registry data. Cancer 2013;119(15 suppl):2820–33. © 2013 American Cancer Society . Abstract : The Centers for Disease Control and Prevention designed and established a 4‐year Colorectal Cancer Screening Demonstration Program (CRCSDP) in 2005 for low‐income, under‐insured or uninsured men and women aged 50 to 64 years in 5 participating US program sites. This report documents the successful implementation of the CRCSDP and describes the clinical outcomes of this 4‐year initiative, patterns in program uptake and test choice, challenges in implementation of fecal occult blood test screening programs, and comparative test performance characteristics of fecal occult blood testing versus colonoscopy.